The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0034-89102008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Programa Saúde da Família e condições sensíveis à atenção primária, Bagé (RS)

Abstract: OBJECTIVE: Ambulatory care-sensitive conditions (ACSC) are health problems managed by actions at the fi rst level of care. The need for hospitalization by these causes is avoidable through an effective and proper primary health care. The objective of the study was to estimate ACSC among patients hospitalized by the Sistema Único de Saúde (Brazilian Health System). METHODS:Hospital-based cross-sectional study involving 1,200 inhabitants of Bagé (Southern Brazil) who were inpatients between September/2006 and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
2
37

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 21 publications
(11 reference statements)
2
43
2
37
Order By: Relevance
“…In a study performed in Brazil, 1 this proportion was 28.5%, slightly higher than the data found for the DF. In Bagé, 9 however, the results contrast with those reported previously and indicate that 42.6% of hospitalizations were due to ACSC. Similarly to the DF, the most frequent cause of hospitalization due to ACSC in Brazil 1 was gastroenteritis, followed by heart failure and bacterial pneumonia.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In a study performed in Brazil, 1 this proportion was 28.5%, slightly higher than the data found for the DF. In Bagé, 9 however, the results contrast with those reported previously and indicate that 42.6% of hospitalizations were due to ACSC. Similarly to the DF, the most frequent cause of hospitalization due to ACSC in Brazil 1 was gastroenteritis, followed by heart failure and bacterial pneumonia.…”
Section: Discussioncontrasting
confidence: 95%
“…5,8,9 Through a literature review on hospitalizations for ACSC and the exposure to at least one characteristic of primary health care (18 articles in the past 13 years) it has been found that most studies pointed to a protective association of variables of structure, process and performance of primary care services, in relation to the risk of hospitalizations due to ACSC. 8 Preventive consultations (sporadic or not), vaccines and ongoing child health care were associated, in various studies, with lower risk of hospitalization due to ACSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a menor formação escolar diminui as chances de emprego, e os desempregados tendem a retardar a busca por cuidados de saúde. Essa associação entre baixa escolaridade e aumento das ICSAP também foi encontrada por outros autores 21,22 . O achado, neste estudo, de maior número de ICSAP associadas à maior urbanização pode sugerir que a residência em aglomerados urbanos, nos quais, em geral, estão localizados os hospitais, facilita o acesso a eles, e, conforme aponta o estudo de Márquez-Calderón et al 8 , o maior acesso aos serviços de urgência e de emergência hospitalares em detrimento da atenção básica colabora para o aumento das hospitalizações sensíveis, pois a atenção secundária e terciária passam a ser a porta de entrada do sistema de saúde.…”
Section: Discussionunclassified
“…5,12 Among the ineffi cient municipalities, 387 hospitalizations were observed. To achieve effi ciency in results, it would be necessary that 250.6 potentially avoidable hospitalizations had not occurred, that is, 64.8% could have been prevented in these municipalities, in case they had adopted the benchmarks' practices.…”
Section: Discussionmentioning
confidence: 99%